A morphometric analysis of pedicles of lumbar vertebrae by using computed tomography scan - Mansur, Dil Islam; Karki, Subindra; Mehta, Dilip Kumar; Shrestha, Pragya; Maskey, Sunima (Journal of Kathmandu Medical College, 2020)
Background: The vertebral column is the central pillar of the body which has cervical, thoracic, lumbar, sacral and coccygeal parts. Out of these, the lumbar part is made up of five lumbar vertebrae which lies between the thoracic part above and the sacral part below. Objective: The study aimed to measure pedicle dimensions of lumbar vertebrae by using computed tomography scan. Methodology: This is a descriptive cross-sectional study which was conducted on 115 images of computed tomography scan collected from the Department of Radio-Diagnosis, Dhulikhel Hospital between May and October 2019 after receiving ethical approval from the Institutional Review Committee. All the scans available in the department were taken for the study. Point estimate at 95% Confidence Interval was calculated along with frequency and proportion for binary data. Data analysis was done in the Statistical Package for the Social Sciences version 16 (SPSS 16.0). Results: The pedicle chord length and breadth progressively decrease from L1 to L5 vertebral levels and pedicle thickness gradually increases from L1 to L5 vertebrae on both sides in both genders. The pedicle chord lengths were found significantly different whereas breadth and thickness were insignificantly different between males and females at all lumbar vertebral levels except at L1 for breadth. Conclusions: The pedicle chord length and breadth gradually decreases whereas thickness increases from L1 to L5 vertebral levels amongst Nepalese population.